Gravidez tardia: bem-estar subjetivo e percepção da gestação - Oliveira, Maria Aurelina Machado de (2012)
The subjective well- being (SWB) is formed by global judgments of satisfaction with life, or with peculiar domains the positive and the negative emotional experiences. The perception in turn, is the process of interpretive process of sensory data with cognitive or informative sense, absorbed in function of a context. From this perspective, the research aimed to evaluate SWB and the perception of advanced age pregnant women. Participated in the survey 80 pregnant with 35 years old or older (Group A or older) and 80 pregnant aged between 20 and 34 years old (Group B or young adults). The instruments used were: the scale of subjective well-being and a questionnaire, that included sociodemographic informations, items about pregnancy and a statement based on the Free Association of Words Technique (FAWT) to approach the perception of pregnancy. The data from the questionnaire and scale, in order to compare the data between groups suffered descriptive and inferential statistical analyzes. The analyzes performed with chi-square test among groups, which had values that were statistically significant, with the sociodemographic variables the type of contraceptive and health problems. The indicators of the SWB had further more by means in groups. The results of the Wilcoxon's test that there were no differences between the groups referred above. In the relation indicators of well being with variables age, education and income, some associations were significant. In addition, the words derived from the (FAWT) were analyzed using the software Programmer s Permenttant l´Analyse des Evocation (EVOC2000) and categorized according to content analysis of Bardin in three thematic categories (positive and negative affects, perception of gestation and implications of pregnancy) discussed as a group, since most of words were common. The study highlights shown how similar were the presented data by pregnant women surveyed. It is supposed about this fact the similarity is related to the social context. The relevance of this study for the health care network is to help with proposals aimed at specific improvements to the public and the sector, beside demonstrate that advanced age pregnant women and young adulst in the researched context showed no differences in the most of the studied characteristics